Automatic Bamboo Fed Type Cutting Mechanism Prototype - Shaari, Muhammad Farid; Raman, Fakrul Nur Aiman; Roslan, Mohd Nazrul; Kamarudin, Khairu; Mohd Razali, Fathee Aizat; Baharuddin, Norhazaedawati (International Journal of Integrated Engineering, 2025)
Currently, most of the bamboo cutting process is done manually. However, the growing demand for bamboo products and the high cost of labor in some countries requires automatic bamboo cutting machine to increase the production rate. The aim of this project was to develop a bamboo cross cutting mechanism prototype which is controlled by Programmable Logic Controller (PLC). Structural design work was carried out using Finite Element Analysis (FEA) to determine the stability and reliability of this prototype. The cutting mechanism was designed to cut bamboo stem at specific length uniformly. It consists of a rotary disc cutter which is powered by a 240VAC motor, bamboo stem positioner and chain-type feeding system. The feeding mechanism feeds the bamboo stem to the rotary cutter in a proportional manner. Once assembled, the prototype underwent for system verification and production rate was calculated to determine its processing capacity. The result shows this prototype has cut length offset at 2.3 cm in average and the production rate was approximately 15.3 cuts per minute or 943.3 cuts per hour in average. The cut length offset is quite wide and can be improved by redesigning the bamboo stem positioner mechanism.